High‐Current‐Density HER Electrocatalysts: Graphene‐like Boron Layer and Tungsten as Key Ingredients in Metal Diborides. Issue 16 (10th July 2019) - Park, Hyounmyung; Zhang, Yuemei; Lee, Eunsoo; Shankhari, Pritam; Fokwa, Boniface P. T.
Abstract: Transition‐metal borides belong to a small class of non‐noble‐metal electrocatalysts that exhibit excellent activity toward the hydrogen evolution reaction (HER) already in bulk form; those containing graphene‐like (flat) boron layers, such as α‐MoB2, are particularly promising. In this study, the first tungsten‐based boride HER electrocatalysts were studied experimentally and theoretically. Tungsten, the diborides of which (α‐ and β‐WB2 ) contain both the active graphene‐like (flat) boron layer and the less active phosphorene‐like (puckered) boron layer, could be successfully substituted (up to 30 at %) for molybdenum in α‐MoB2 . The resulting α‐Mo1− x Wx B2 exhibited better HER activity and stability than the binaries WB2 and MoB2, especially at high current density in acidic electrolytes. DFT calculations showed that the graphene‐like boron layer is the most active among the studied surfaces and that tungsten promotes hydrogen generation by facilitating bonding between hydrogen atoms in contrast to molybdenum. These results should pave the way for high‐current‐density, abundant, and inexpensive bulk and nanoscale HER catalysts by applying structure–activity relationships. Abstract : Working in synergy : Combining experiments and theoretical calculations, it is shown that in the highly active hydrogen evolution catalyst α‐Mo0.7 W0.3 B2, molybdenum is crucial to the stability of the most active graphene‐like (flat) boron layer whereas tungsten promotes hydrogen generation by facilitating bonding between the hydrogen atoms.